Integrated genomic analysis identifies novel low-frequency cis-regulatory variant rs2279658 associated with VSD risk in Chinese children - Jin, Lihui; Han, Zhenyuan; Jiang, Zhongli; Lu, Jieru; Wu, Yizhuo; Yan, Bingqian; Zhang, Weibin; Lin, Xuedong; Jiang, Lvyan; Zhao, Pengjun; Sun, Kun (Frontiers in Cell and Developmental Biology, 2022)
VSD combined with other cardiac or extracardiac malformations (defined as ‘complex VSD’ by us) is one of the major causes of perinatal morbidity and mortality. Functional non-coding SNPs (cis-regulatory SNPs) have not been systematically studied in CHDs, including complex VSD. Here we report an exome-wide association analysis using WES data of 60 PA/VSD cases, 20 TOF cases and 100 controls in Chinese children. We identify 93 low-frequency non-coding SNPs associated with complex VSD risk. A functional genomics pipeline integrating ATAC-seq, ChIP-seq and promoter CHi-C recognizes the rs2279658 variant as a candidate cis-regulatory SNP. Specifically, rs2279658 resides in a cardiac-specific enhancer bound by FOXH1 and PITX2, and would abrogate binding of these two transcription factors to the identified enhancer during cardiac morphogenesis. COQ2 and FAM175A are predicted to be target genes for ‘rs2279658-FOXH1 or PITX2’ pairs in the heart. These findings highlight the importance of cis-regulatory SNPs in the pathogenesis of complex VSD and broaden our understanding of this disease.